Faunist Analysis of Phytonematodes of Corn Plant in The Southern Territory of Surkhandara Region - Iskandarova Nilufar Ergashevna; Iskandarova Irodaxon Ergashevna; Asallayev Uktam Hayriddinovich (Zien Journals, 2021)
In the southern parts of Surkhandarya region, a comprehensive study of the complex of nematode fauna of grain crops, including corn, and the identification of disease-causing species, the fight against parasitic species in increasing the yield of corn the basis of these data measure is the development of measures
Keywords: Nematodafauna; saynxorst metodi; Merlinius dubius; Helicotylenchus pseudorobustus